2016
DOI: 10.1007/s11258-016-0614-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between foliar carbon isotope composition and elements of C3 species in grasslands of Inner Mongolia, China

Abstract: Foliar elements and their ratios can be related to foliar carbon isotope composition (d 13 C) through their involvement in plant transpiration, photosynthesis, and osmotic adjustment. In order to investigate these relationships in grasslands of Inner Mongolia, China, d13 C and element contents of dominant C 3 species at 47 grassland sites were determined. For C 3 species, d13 C showed no correlation with carbon (C), positive correlations with nitrogen (N), nitrogen:phosphorus ratio (N/P) and carbon:phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 47 publications
(79 reference statements)
4
8
0
Order By: Relevance
“…Multiple studies have reported various correlations between the δ 13 C and leaf nutrients [20,21,38]. In the present work, the positive relationship between δ 13 C and N over all aged leaves together (Table 2) is in accordance with most previous studies [20,39].…”
Section: Relationships Between the δ 13 C δ 15 N Values And Leaf Nutsupporting
confidence: 92%
See 3 more Smart Citations
“…Multiple studies have reported various correlations between the δ 13 C and leaf nutrients [20,21,38]. In the present work, the positive relationship between δ 13 C and N over all aged leaves together (Table 2) is in accordance with most previous studies [20,39].…”
Section: Relationships Between the δ 13 C δ 15 N Values And Leaf Nutsupporting
confidence: 92%
“…Our study observed that leaf δ 13 C was positively related to all aged leaves' P concentrations in simple regression (Table 2), but the effect of leaf P concentration on δ 13 C was not significant in multiple regression ( Figure 4A). This indicates that the variations in the leaf δ 13 C values were likely caused by stomatal limitation rather than P-related changes in photosynthetic efficiency [18,20]. In addition, our findings of the negative correlation between leaf δ 13 C and the C:N ratios is consistent with the results from multiple previous studies and suggests that P. crassifolia may achieve higher water use efficiency (WUE) at the expense of decreased nitrogen use efficiency (NUE) [20,38].…”
Section: Relationships Between the δ 13 C δ 15 N Values And Leaf Nutsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, our results indicated that leaf δ 13 C showed a negative relationship with N and P concentrations for all species, which has also been observed in several previous studies [28,40,41,[63][64][65]. Moreover, the negative correlation between leaf δ 13 C and leaf N concentration is reported to be independent of functional group, vegetation type, and altitude, suggesting that this is a general trend for plants [66,67]. Other studies have interpreted the negative correlation between leaf δ 13 C and leaf N concentration as an autocorrelation due to low water availability in semi-arid environments [63,67].…”
Section: Variation In Leaf δ 13 C Of Three Caragana Species Along Thesupporting
confidence: 89%